Rancang Bangun Alat Deteksi Salmonella sp. pada Susu Berbasis Electronic Nose - Safari, Wulan Fitriani (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2025)
Contamination of pathogenic bacteria in milk can cause milk spoilage and become a gateway for disease transmission to humans. Salmonella sp. is one of the pathogenic bacteria that contaminates milk and can be transmitted to humans who consume the milk. The safety of milk in relation to foodborne diseases is an important thing to consider. Therefore, it is necessary to examine the contamination of pathogenic bacteria in milk. The purpose of this study was to design a Salmonella sp. detection tool in milk based on Electronic Nose (E-nose). The research was carried out through several stages, namely making block diagrams, mechanical design, Arduino design and tool testing. The design of the tool made using the MQ-136 sensor which will detect Hydrogen Sulfide (H2S) gas. The results of the tool test showed the reading results of the MQ-136 sensor for milk without Salmonella sp. culture of 92-118 ppm while the reading of the MQ-136 sensor for milk given Salmonella sp. culture was 126-166 ppm. The design of the Salmonella sp. detection tool in milk based on the electronic nose was successfully made. The test results showed that there was a difference in the reading results of the MQ-136 sensor.